A Twin S‐Scheme Artificial Photosynthetic System with Self‐Assembled Heterojunctions Yields Superior Photocatalytic Hydrogen Evolution Rate. Issue 6 (18th December 2022) - Ruan, Xiaowen; Huang, Chengxiang; Cheng, Hui; Zhang, Zhiquan; Cui, Yi; Li, Zhiyun; Xie, Tengfeng; Ba, Kaikai; Zhang, Haiyan; Zhang, Lei; Zhao, Xiao; Leng, Jing; et al.
Abstract: Designing heterojunction photocatalysts imitating natural photosynthetic systems has been a promising approach for photocatalytic hydrogen generation. However, in the traditional Z‐Scheme artificial photosynthetic systems, the poor charge separation, and rapid recombination of photogenerated carriers remain a huge bottleneck. To rationally design S‐Scheme (i.e., Step scheme) heterojunctions by avoiding the futile charge transport routes is therefore seen as an attractive approach to achieving high hydrogen evolution rates. Herein, a twin S‐scheme heterojunction is proposed involving graphitic C3 N4 nanosheets self‐assembled with hydrogen‐doped rutile TiO2 nanorods and anatase TiO2 nanoparticles. This catalyst shows an excellent photocatalytic hydrogen evolution rate of 62.37 mmol g −1 h −1 and high apparent quantum efficiency of 45.9% at 365 nm. The significant enhancement of photocatalytic performance is attributed to the efficient charge separation and transfer induced by the unique twin S‐scheme structure. The charge transfer route in the twin S‐scheme is confirmed by in situ X‐ray photoelectron spectroscopy (XPS) and electron spin resonance (ESR) spin‐trapping tests. Femtosecond transient absorption (fs‐TA) spectroscopy, transient‐state surface photovoltage (TPV), and other ex situ characterizations further corroborate the efficient charge transport across the catalyst interface. This work offers a new perspective on constructing artificial photosynthetic systems with S‐scheme heterojunctions to enhance photocatalytic performance. Abstract : Solar hydrogen generation using heterojunction photocatalysts imitating natural photosynthetic systems is fast emerging. The poor charge separation and futile charge transports routes in Z‐Scheme heterojunctions; however, constitute a huge bottleneck for hydrogen evolution. A Twin S‐Scheme artificial photosynthetic system is developed to overcome this bottleneck, which yields an outstanding hydrogen evolution rate and high apparent quantum efficiency.